2017
DOI: 10.4067/s0718-50062017000100004
|View full text |Cite
|
Sign up to set email alerts
|

Invarianza Factorial de la Escala de Ansiedad ante el Envejecimiento de Lasher y Faulkender en Estudiantes Universitarios, Hombres y Mujeres

Abstract: * Autor a quien debe ser dirigida la correspondencia.Recibido May. 16, 2016; Aceptado Jul. 20, 2016; Versión final Sep. 14, 2016, Publicado Feb. 2017 Resumen El presente estudio analiza las propiedades psicométricas de la Escala de Ansiedad ante el Envejecimiento en hombres y mujeres universitarios. La muestra total fue de 1703 participantes; 878 mujeres y 825 hombres, con una edad media de 20.5 años y 20.9 años, respectivamente. Los análisis factoriales confirmatorios mostraron que una estructura tetrafactori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
2
4
0
Order By: Relevance
“…The results of model fit indices in CFA show the revised 17-item AAS has good four-factor model fit among Malaysian youths. This finding demonstrates that AAS is a multidimensional construct consistent with the original scale and other several AAS validation studies (Aguirre et al, 2017;Gao, 2012;Koukouli et al, 2014;Lasher & Faulkender, 1993;Ornelas et al, 2016;Sargent-Cox et al, 2014). The total variance extracted was high with amount of 59.1% supporting for content validity of the questionnaire.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The results of model fit indices in CFA show the revised 17-item AAS has good four-factor model fit among Malaysian youths. This finding demonstrates that AAS is a multidimensional construct consistent with the original scale and other several AAS validation studies (Aguirre et al, 2017;Gao, 2012;Koukouli et al, 2014;Lasher & Faulkender, 1993;Ornelas et al, 2016;Sargent-Cox et al, 2014). The total variance extracted was high with amount of 59.1% supporting for content validity of the questionnaire.…”
Section: Discussionsupporting
confidence: 84%
“…The AAS is a 20-item instrument developed based on multidimensional aging anxiety and has a four-factor model namely Fear of Old People, Psychological Concerns, Physical Appearance and Fear of Loss (Lasher & Faulkender, 1993). AAS validity and reliability has been established by its original authors and other previous studies among volunteer adults, university students, healthcare professional and community students (Aguirre, Ornelas, Gastélum, & Peinado, 2017;Gao, 2012;Koukouli, Pattakou-Parasyri, & Kalaitzaki, 2014;Lasher & Faulkender, 1993;Lynch, 2000;Ornelas, Gastélum, Lopez-Walle, & Rodríguez-Villalobos, 2016;Sargent-Cox, Rippon, & Burns, 2014). However, there has been lacking proper validation of AAS in Asiatic region.…”
Section: Anxiety About Aging Scale (Aas)mentioning
confidence: 99%
“…In addition to the fact that the comparisons between the groups reflected significant differences in one of the factors (Fear of the Elderly), which seems to indicate that older adult men in comparison with their female counterparts, tend to present higher levels of anxiety about aging in relation to the anxiety generated by external contact with others. Which, in general, agrees with findings reported by Aguirre, et al [ 33 ] who state that women show more anxiety in relation to decision-making or the loss of the meaning of life as an older adult, while men do so in relation to living with older adults.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies have corroborated the factorial structure found by the authors of the scale [18,[27][28][29][30][31], although discrepancies have been found in the number and meaning of items according to age and gender when adapting the instrument to different contexts [18,32].…”
Section: Introductionmentioning
confidence: 67%